Ankylosaurus and other armored dinosaurs the need-to-know facts - Clay, Kathryn (North Mankato, MN Capstone Press, 2016)
Full-color images and simple text introduce young readers to different armored dinosaurs, including their physical characteristics, habitats, and diets"--
Science ( Animals)
a gift from book africa
1 2 13 15
Keywords: Ankylosaurus -- Juvenile literature; Armored animals -- Juvenile literature; Dinosaurs -- Juvenile literature